Legal Protection for Customer Funds Against False Accounting by the President Director of PT. BPR Kuda Mas Sentosa (Case Study Decision Number: 457/PID/2019/PT SBY) - Waldo, Risky (Yayasan Sinergi Kawula Muda, 2023)
Banks, as financial institutions, function as both aggregators and distributors of funds from the public. In the interest of security, people often opt to deposit their money in banks. Various banking products are offered, including current accounts, fixed deposits, certificates of deposit, and savings accounts. However, banks sometimes commit violations that result in losses for their customers. The relationship between banks and customers is based on contractual agreements. This research is conducted due to cases involving the disappearance of customer savings within PT. BPR KUDA MAS SENTOSA in Porong, Sidoarjo, involving internal bank actors. Banking laws do not explicitly address the bank's responsibility when it acts beyond its authority. It is essential for banks, as parties with a relationship between them and customers, to provide legal protection for customers. This study falls under normative legal research, using primary, secondary, and tertiary legal materials collected through literature review. Qualitative analysis is employed, focusing on legal regulations and case studies, examining how these norms are applied in banking practices. The findings reveal that banks, being institutions trusted by the public, must be held accountable for the loss of customer savings, as failing to do so erodes the trust placed in them by the public. Customers are entitled to legal protection, which banks must provide as part of their responsibilities.